Microduplication of 3p26.3 Implicated in Cognitive Development - Leah Te Weehi; Raj Maikoo; Adrian Mc Cormack; Roberto Mazzaschi; Fern Ashton; Liangtao Zhang; Alice M. George; Donald R. Love (Case Reports in Genetics)
We report here a 34-month-old boy with global developmental delay referred for molecular karyotyping and fragile X studies. Molecular karyotype analysis revealed a microduplication in the 3p26.3 region involving part of the CHL1 and CNTN6 genes. Several deletions, one translocation, and one duplication have previously been described in this region of chromosome 3. The CHL1 gene has been proposed as a dosage-sensitive gene with a central role in cognitive development, and so the microduplication reported here appears to be implicated in our patient’s phenotype.